Experimental investigation on thermal effects in picosecond laser drilling of thermal barrier coated In718. (May 2019) - Sun, Xiaomao; Dong, Xia; Wang, Kedian; Wang, Rujia; Fan, Zhengjie; Duan, Wenqiang
Highlights: Repetition frequency was found to affect heat accumulation most significantly. Plasma reheating and lattice heat accumulation are the main causes of defects. The distribution, thickness and formation mechanism of resolidified layer differ from recast layer. Abstract: Multilayer material drilling is an important technology in the machining of film cooling holes. In this paper, trepanning drilling of thermal barrier coated In718 with 532 nm picosecond laser was investigated with emphasis on thermal effects. We discussed the relationship between heat accumulation and processing parameters as well as the formation mechanism of resolidified layer. According to the experimental result, the repetition rate is the most significant factor to affect heat accumulation. By discussing the influence of repetition rate on plasma reheating and heat transfer-dissipation of the lattice, the formation mechanism of molten material accumulation around the entrance as well as the mechanism of the cylinder at the center of the hole was explained. Further study on defects of the side wall revealed the existence of a thin intermittent resolidified layer, which is quite different from the recast layer in long pulsed laser drilling. The difference in material removal mechanisms was the primary cause of this phenomenon. Discussion of this difference can provide references to the formation of defects as well as improve processing quality in the process of picosecond laser drilling on thermal barrier coated alloy.